Traditional Knowledge and Molecular Evidence of Medicinal Plants for Multi-Target Dengue Therapy: A Review - Mohammed Anas; Farhat Jahan (Tropical Journal of Pharmaceutical and Life Sciences, 2026)
Dengue fever continues to intensify as a major global public health challenge, driven by climate change, rapid urbanization, and expanding vector habitats, while the absence of a universally safe and effective antiviral therapy remains a critical limitation. Unlike conventional single-target antivirals, plant-based interventions offer a multi-target therapeutic strategy capable of simultaneously inhibiting viral replication, modulating immune dysregulation, reducing oxidative stress, stabilizing endothelial function, enhancing platelet recovery, and contributing to vector control. A wide range of phytochemicals, including flavonoids, alkaloids, tannins, polyphenols, polysaccharides, and bioactive enzymes, have been reported to interact with key dengue viral proteins such as NS2B-NS3 protease and NS5 RNA-dependent RNA polymerase, while also regulating host inflammatory and immunological pathways. Integration of ethnopharmacological data with molecular docking, network pharmacology, and preclinical studies provides mechanistic validation for traditionally used plants, particularly Carica papaya, Andrographis paniculata, and Tinospora cordifolia. Additionally, analysis of plant diversity, parts used, phytochemical classes, and conservation status highlights both therapeutic promise and sustainability concerns. Despite promising in-vitro and in-silico evidence, clinical translation remains constrained by lack of standardized formulations, limited in-vivo validation, and insufficient large-scale clinical trials. This review comprehensively integrates epidemiological trends, dengue virus biology, pathogenesis, traditional knowledge, and modern molecular evidence to evaluate the therapeutic potential of medicinal plants in dengue management. Overall, this review underscores medicinal plants as evidence-based, multi-target candidates for next-generation dengue therapeutics, offering a sustainable and affordable pathway to mitigate the escalating global dengue burden.